The impact of the war with Russia on the development of transport in Ukraine - Kersys, Robertas; Pererva, P. G.; Kobielieva, Tetiana (Teadmus OÜ, Estonia, 2024)
The report proves that the war with Russia has become a serious challenge for Ukraine's transport system, but at the same time it has stimulated reforms, integration with European infrastructure, new logistics approaches and the development of alternative routes. This allows Ukraine to gradually strengthen its transport independence, although long-term recovery requires significant investment and international support.
Keywords: transport industry; Ukraine; russia's war with Ukraine; damage; restoration; development prospects